Lactate-related metabolic reprogramming and immune regulation in colorectal cancer - Sun, Qianhui; Wu, Jingyuan; Zhu, Guanghui; Li, Tingting; Zhu, Xiaoyu; Ni, Baoyi; Xu, Bowen; Ma, Xinyi; Li, Jie (Frontiers in Endocrinology, 2023)
Changes in cellular metabolism involving fuel sources are well-known mechanisms of cancer cell differentiation in the context of carcinogenesis. Metabolic reprogramming is regulated by oncogenic signaling and transcriptional networks and has been identified as an essential component of malignant transformation. Hypoxic and acidified tumor microenvironment contributes largely to the production of glycolytic product known as lactate. Evidence describing the roles of lactate in the CRC tumor microenvironment in the regulation of metabolism, immune response, and intercellular communication has accumulated in recent years. This article reviews recent progress in the pleiotropic effects of lactate in the colorectal cancer tumor microenvironment and the clinical value of targeting lactate metabolism as part of treatment.. Current evidence suggests that lactate exerts different effects according to different immune cell types, microenvironment, and pathophysiological processes. In addition, multiple therapeutic targets, including epigenetic modification and the activation of transcription factors such as LDH, MCT, PI3K/AKT, NF-κB and HIF-1, enable lactate to regulate the immune metabolism of CRC cells, which could provide novel therapeutic strategies for enhancing anti-tumor effects and reversing drug resistance in CRC. Future studies are still needed.